The Intitutional Transformation of Merah Putih Coorperative - Chariel Arthurochman; Syeh Nur Alief Al Ghozali (Fakultas Kewirausahaan Universitas Garut, 2026)
This study analyzes the effectiveness of the Koperasi Kelurahan Merah Putih in Surabaya as an institutional solution to urban competitiveness challenges. Amidst Surabaya's economic growth of 5.76%, the primary challenge for its 12,320 MSMEs is the penetration of modern retail and fintech. Utilizing the framework of Economic Institutionalism Theory, this research examines six strategic innovations, including the transformation of cooperatives into B2B aggregators, the integration of the Simkopdes system with the E-Peken platform, and the Credit Plus Mentoring model. The analysis results indicate that cooperatives functioning as